Linguistic Features and Conversational Functions of the Tosa Dialect in Gintama - Julia, Julia; Arfianty, Rani (Chi e Journal of Japanese Learning and Teaching, 2025)
This study examines the linguistic forms and conversational functions of the Tosa dialect as represented in the anime Gintama. Originating from Kochi Prefecture, the Tosa dialect preserves elements of ancient Western Japanese in both phonologu and vocabulary, contributing to its distinct linguistic character. In Gintama, the dialect is used to construct character identity and highlight regional background, particularly for figures modeled after historical personalities from Tosa. Drawing on qualitative and descriptive methods, this study analyzed dialogues spoken by characters who use the Tosa dialect across several episodes. The analysis identifies seventeen dialectal forms, including grammatical variations such as ~yuu , ~chuu, ~ki, and ~jaki, and explores their pragmatic roles in expressing aspect, negation, emphasis, and causality. The findings reveal how dialectial variation contributes to characterization and authenticity in Japanese popular media. Despite notable differences from standard Japanese, the contextual use of the Tosa dialect in Gintama allows viewers to infer meaning and appreciate the cultural and linguistic diversity it represents .